An Exact and Practical Analyzing Model for Radial Vibration of Piezoelectric Spherical Transducers With Arbitrary Wall Thickness - Wang, Sha (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2021)
The piezoelectric spherical transducers have attracted extensive attention in hydroacoustics and health monitoring. However, most reported piezoelectric spherical transducers are merely analyzed by the thin spherical shell theory, which is unsuitable for the gradually increased spherical shell thickness. Therefore, it is necessary to develop the radial vibration theory of the piezoelectric spherical transducer with arbitrary wall thickness. Herein, an exact analyzing model for the radial vibration of the piezoelectric spherical transducer with arbitrary wall thickness is proposed. The radial displacement and electric potential for radial vibration of the piezoelectric spherical transducer are precisely given, and then, the electromechanical equivalent circuit is obtained. Based on the electromechanical equivalent circuit, the resonance/antiresonance frequency equations of piezoelectric spherical transducers in the radial vibration are obtained. Besides, the relationship between performance parameters and wall thicknesses is discussed. The wall thickness has a significant influence on the performance parameters of the spherical transducer. The accuracy of the theory is validated by comparing the results with the experiment and finite element analysis